ANALISIS GEOMEKANIKA FORMASI HALANG DI DAERAH STRUKTUR GEOLOGI SEKITAR SUNGAI CITAAL, KUNINGAN, JAWA BARAT - -, Zufialdi Zakaria (Bulletin of Scientific Contribution, 2006)
Lithology at research area consist of sandstone, claystone and brecia which include to Halang Formation. Structure of geology is sinistral strike-slip fault with relative strike to southwest - northeast. Geomechanic analysis given a number of Rock Mass Rating and Slope Mass rating as follows: Rock mass rating is 55 to 66. RMR to foundation is 48 to 50. Description of class number is 3 (III), its mean fair rock.Slope mass rating given number of slope angle which is suggested to stable slope, as follows: According to Laubscher (1975) SMR is 55o. According to Hall (1985) SMR is 56.20o to 63.35o. According to Orr (1992) SMR is 64.49o to 71.71o . Environmental management is preventive effort of impact which attend with foundation design according to allowable bearing capacity and / or choice the architecture of building to safety. Monitoring can be conducted to condition of building (house, bridge, drainage etc.)